(untitled) (Research, Society and Development, 2021)
This research aimed to analyze the Brazilian scientific production regarding work in educational groups carried out in Primary Care between 2009 and 2018, highlighting the potential and difficulties encountered by professionals and the contributions of the groups from the implementation of the Expanded Center for Family Health and Primary Care. This is an Integrative Literature Review whose search took place in the Virtual Health Library from the combination of nine keywords in eight intersections, resulting in 220 studies. Eighteen studies were selected, most of which used a qualitative methodology and approached health professionals. As for the place of publication, the Brazilian region with the greatest contribution was the Northeast, whereas in the North and Midwest the theme is little explored. The journal with the greatest contribution was Ciência e Saúde Coletiva. The highlighted potentials were:exchange of experience between users; realization by a multidisciplinary team; link between professional and user; use of community spaces. As difficulties, the following stand out: inadequate structure; low adherence of professionals and users; lack of understanding of management; lack of formal referral, lack of organization regarding periodicity, schedule and planning. As for the Expanded Family Health Center, its work in Primary Care and its partnership with the Family Health Teams was evaluated. Working in groups in Primary Care brings countless potentials and difficulties, making it necessary for professionals to be able to deal with such mishaps. It was noticed that where there is multiprofessional work, good results are collected, therefore, joint planning is necessary.